Perioperative chemotherapy for resectable colorectal liver metastases: Analysis from the Colorectal Operative Liver Metastases International Collaborative (COLOMIC). Issue 2 (16th April 2022) - Gawdi, Rohin; Valenzuela, Cristian D.; Moaven, Omeed; Stauffer, John A.; Del Piccolo, Nico R.; Cheung, Tanto; Corvera, Carlos U.; Wisneski, Andrew D.; Cha, Charles; Russell, Greg; Zarandi, Nima; Dourado, Justin; et al.
Abstract: Background: Chemotherapy has been increasingly combined with surgery as multimodality treatment for resectable colorectal‐liver metastases (CLM). There is paucity of clinical data addressing optimal timing of chemotherapy relative to surgery. We examined outcomes of patients undergoing hepatectomy for resectable CLM. Methods: Seven hundred and eighteen patients treated with hepatectomy for CLM were analyzed from five hepatobiliary institutions between 2000 and 2018. Overall survival (OS) was measured from time of hepatectomy for patients receiving: surgery alone, neoadjuvant, adjuvant, and neoadjuvant‐plus‐adjuvant (perioperative) chemotherapy. Kaplan–Meier analysis was performed to detect differences in OS between treatment groups. Single‐ and multi‐variable analysis with Cox proportional hazards were run for OS between groups. Results: One hundred and thirty‐seven patients (19.08%) received surgery, 104 (14.48%) received neoadjuvant‐only, 214 (29.81%) received adjuvant‐only, and 263 (36.63%) received perioperative chemotherapy; with median OS of 48.20, 46.83, 56.27, and 49.93 months, respectively. No differences in median OS were seen between groups on Kaplan–Meier analysis. No significant difference in Charlson‐Deyo comorbidity status was seen between groups ( p = 0.853), while significant difference was seen in maximum tumor size ( p = 0.0023). On multivariate analysis, adjuvant ( p = 0.010) and perioperative ( p = 0.020) chemotherapy were independently associated with OS compared to surgery alone. Discussion: Despite group differences, chemotherapy after surgery was independently associated with improved OS in CLM.